Combinatorial peptides: A library that continuously probes low‐abundance proteins. Issue 1 (20th September 2021) - Boschetti, Egisto; Zilberstein, Gleb; Righetti, Pier Giorgio
Abstract: After a decade of experimental applications, it is the objective of this review to make a point on combinatorial peptide ligand libraries dedicated to low‐abundance proteins from animals to plants and to microorganism proteomics. It is, thus, at the light of the recent technical developments and applications that we will examine the state of the art, its usage within the scientific community, and its openness to unexplored fields. The improvements of the methodology and its implementation in connection with analytical determinations of combinatorial peptide ligand library (CPLL)‐treated samples are extensively reviewed and commented upon. Relevant examples covering few critical aspects describe the performance of the technology. Finally, a reflection on the technological future is attempted in particular by involving new concepts adapted to the limited availability of certain biological samples.